Use of Nanopore Sequencing to Characterise the Genomic Architecture of Mobile Genetic Elements Encoding blaCTX-M-15 in Escherichia coli Causing Travellers’ Diarrhoea - Bird, Matthew T.; Greig, David R.; Nair, Satheesh; Jenkins, Claire; Godbole, Gauri; Gharbia, Saheer E. (Frontiers in Microbiology, 2022)
Increasing levels of antimicrobial resistance (AMR) have been documented in Escherichia coli causing travellers’ diarrhoea, particularly to the third-generation cephalosporins. Diarrhoeagenic E. coli (DEC) can act as a reservoir for the exchange of AMR genes between bacteria residing in the human gut, enabling them to survive and flourish through the selective pressures of antibiotic treatments. Using Oxford Nanopore Technology (ONT), we sequenced eight isolates of DEC from four patients’ specimens who had all recently returned to the UK from Pakistan. Sequencing yielded two DEC harbouring blaCTX-M-15 per patient, all with different sequence types (ST) and belonging to five different pathotypes. The study aimed to determine whether blaCTX-M-15 was located on the chromosome or plasmid and to characterise the drug-resistant regions to better understand the mechanisms of onward transmission of AMR determinants. Patients A and C both had one isolate where blaCTX-M-15 was located on the plasmid (899037 & 623213, respectively) and one chromosomally encoded (899091 & 623214, respectively). In patient B, blaCTX-M-15 was plasmid-encoded in both DEC isolates (786605 & 7883090, whereas in patient D, blaCTX-M-15 was located on the chromosome in both DEC isolates (542093 & 542099). The two blaCTX-M-15–encoding plasmids associated with patient B were different although the blaCTX-M-15–encoding plasmid isolated from 788309 (IncFIB) exhibited high nucleotide similarity to the blaCTX-M-15–encoding plasmid isolated from 899037 (patient A). In the four isolates where blaCTX-M-15 was chromosomally encoded two isolates (899091 & 542099) shared the same insertion site. The blaCTX-M-15 insertion site in isolate 623214 was described previously whereas that of isolate 542093 was unique to this study. Analysis of Nanopore sequencing data enables us to characterise the genomic architecture of mobile genetic elements encoding AMR determinants. These data may contribute to a better understanding of persistence and onward transmission of AMR determinants in multi-drug resistant (MDR) E. coli causing gastrointestinal and extra-intestinal infections.